Beban Adminstrasi Keuangan di Badan Keuangan Daerah Kabupaten Semarang - Kalami, Gaung Fathi; Hafani, Hanif (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to identify the financial administration burdens borne by the Semarang Regency Regional Finance Agency and analyse the constraints faced in its management. This research focuses on two main aspects: first, identifying the types of financial administration burden managed by Semarang Regency's Regional Finance Agency, including the collection and management of local revenues, expenditures and disbursements, and financial reporting; second, analysing the constraints that affect the management of financial administration burden, both from internal organisational aspects such as systems and procedures that are not yet well integrated, as well as external factors such as changes in central government policies and regulations that have an impact on local finances. This research uses a qualitative research method with an interview approach as one of the main techniques. Through in-depth interviews with relevant parties, the researcher is expected to gain an in-depth understanding of the dynamics of financial management at the Semarang Regency Regional Finance Agency and extract relevant information to formulate constructive recommendations to improve the efficiency and effectiveness of regional financial management.